Peace Building: Tantangan Dakwah di Era Disrupsi - Nahed Nuwairah (Alhadharah: Jurnal Ilmu Dakwah, 2020)
Since the global challenges of da’wah getting more and complex, it is necessary for  the preachers to understand strategic steps to consider before doing da’wah. Including in Indonesia as a country that has so many diversity of etnicities, tribes, languages, religions and cultures.  Realizing an atmosphere of harmony in Indonesian society requires the togetherness of various community  parties, including   preachers who bear  the responsibility for reflects   the values of Islam as rahmatan li al-‘alamin.     This paper mainly focused on how do da’wah    that can be applied in  Indonesia as a nation  unity in diversity  (Bhinneka Tunggal Ika) in   order to building peace facing the disruption era.  Regarding to  the disruption era, the da’wah approach will require changes and adjustment, both regarding the form, media, content (message)  and underlying paradigm.  The author offers  some  strategies, there are strengthening family,   fostering  common perceptions among  community groups by strengthening  universal  values and   developing an information system that is able to reach people widely and foster effective and harmonious communication. Of course, this writing accompanied by hope that there will be an effort to elaborate it systematically in the future.